Polymorphonuclear Leukocytes or Hydrogen Peroxide Enhance Biofilm Development of Mucoid Pseudomonas aeruginosa - Qi Tan; Qing Ai; Qi Xu; Fang Li; Jialin Yu (Mediators of Inflammation)
Pseudomonas aeruginosa is an opportunistic pathogenic bacterium involved in many human infections, including pneumonia, diabetic foot ulcers, and ventilator-associated pneumonia. P. aeruginosa cells usually undergo mucoid conversion during chronic lung infection in patients with cystic fibrosis (CF) and resist destruction by polymorphonuclear leukocytes (PMNs), which release free oxygen radicals (ROS), such as H2O2. PMNs are the main leucocytes in the CF sputum of patients who are infected with P. aeruginosa, which usually forms biofilms. Here, we report that PMNs or H2O2 can promote biofilm formation by mucoid P. aeruginosa FRD1 with the use of the hanging-peg method. The mucoid strain infecting CF patients overproduces alginate. In this study, PMNs and H2O2 promoted alginate production, and biofilms treated with PMNs or H2O2 exhibited higher expression of alginate genes. Additionally, PMNs increased the activity of GDP-mannose dehydrogenase, which is the key enzyme in alginate biosynthesis. Our results demonstrate that PMNs or H2O2 can enhance mucoid P. aeruginosa biofilms.